Physio Chemical Analysis of ground water from various part of Cuddalore District, Tamil Nadu (India) - R. PAZHANIRAJA,; DR. N. LATHA, (The Bioscan, 2021)
The study evaluation the groundwater quality in the different areas of the Cuddalore district of determine its suitability for drinking and other purposes. The physio chemical properties of a ground water sample from the cuddalore region are compared with standard limits specified by the BIS and the water quality parameters such as PH, TDS, Calcium, Magnesium hardness, Alkalinity and some heavy metals are assessed using Indian Standard Precedents. Based on the result, I was able to confirm that all ten ground water samples that were collected contained harmful substance that could harm humans and animals and be used for other purposes. The results also showed that all of the parameters of the samples were above the BIS standards.